British Sorbus (Rosaceae): Six new species, two hybrids and a new subgenus. - Rich, T.; Green, D.; Houston, L.; Lepší, Martin; Ludwig, S.; Pellicer, J. (Maney Publishing, 2014)
Six new Sorbus species are described in Sorbus subgenus Aria; S. evansii T.C.G. Rich, sp. nov., S. greenii T.C.G. Rich, sp. nov., S. herefordensis D. Green, sp. nov., S. richii L. Houston, sp. nov., S. sellii T.C.G. Rich, sp. nov., and S. spectans L. Houston, sp. nov. The occurrence of two new subgeneric hybrids is noted – S. aucuparia6minima (subgenus Soraria) and a distinct member of subgenus Tormaria of unknown parentage – which do not merit binomials. Subgenus Triparens M. Lepsˇı´ & T.C.G. Rich is described to accommodate taxa that originated as crosses between Sorbus subgenus Aria, subgenus Sorbus and subgenus Torminaria.
Keywords: Britain, Sorbus decipiens, whitebeam